The major thylakoid protein kinases STN7 and STN8 revisited: effects of altered STN8 levels and regulatory specificities of the STN kinases - Wunder, Tobias; Xu, Wenteng; Liu, Qiuping; Wanner, Gerhard; Leister, Dario; Pribil, Mathias (Frontiers in Plant Science, 2013)
Thylakoid phosphorylation is predominantly mediated by the protein kinases STN7 and STN8. While STN7 primarily catalyzes LHCII phosphorylation, which enables LHCII to migrate from photosystem (PS) II to PSI, STN8 mainly phosphorylates PSII core proteins. The reversible phosphorylation of PSII core proteins is thought to regulate the PSII repair cycle and PSII supercomplex stability, and play a role in modulating the folding of thylakoid membranes. Earlier studies clearly demonstrated a considerable substrate overlap between the two STN kinases, raising the possibility of a balanced interdependence between them at either the protein or activity level. Here, we show that such an interdependence of the STN kinases on protein level does not seem to exist as neither knock-out nor overexpression of STN7 or STN8 affects accumulation of the other. STN7 and STN8 are both shown to be integral thylakoid proteins that form part of molecular supercomplexes, but exhibit different spatial distributions and are subject to different modes of regulation. Evidence is presented for the existence of a second redox-sensitive motif in STN7, which seems to be targeted by thioredoxin f. Effects of altered STN8 levels on PSII core phosphorylation, supercomplex formation, photosynthetic performance and thylakoid ultrastructure were analyzed in Arabidopsis thaliana using STN8-overexpressing plants (oeSTN8). In general, oeSTN8 plants were less sensitive to intense light and exhibited changes in thylakoid ultrastructure, with grana stacks containing more layers and reduced amounts of PSII supercomplexes. Hence, we conclude that STN8 acts in an amount-dependent manner similar to what was shown for STN7 in previous studies. However, the modes of regulation of the STN kinases appear to differ significantly.